Does paid sick leave encourage staying at home? Evidence from the United States during a pandemic. (9th March 2023) - Andersen, Martin; Maclean, Johanna Catherine; Pesko, Michael F.; Simon, Kosali
Abstract: We study the impact of a temporary U.S. paid sick leave mandate that became effective April 1st, 2020 on self‐quarantining, proxied by physical mobility behaviors gleaned from cellular devices. We study this policy using generalized difference‐in‐differences methods, leveraging pre‐policy county‐level heterogeneity in the share of workers likely eligible for paid sick leave benefits. We find that the policy leads to increased self‐quarantining as proxied by staying home. We also find that COVID‐19 confirmed cases decline post‐policy.